Evaluation of the relationship between oral health related quality of life and severity of dental caries of pre-school children - shirin taravati; zahra abbasihormozi (Tehran University of Medical Sciences, 2022)
Background and Aims: Dental caries affects the quality of life of children and parents, oral health and overall health which can interfere with the childrens' daily activities and growth. The purpose of this study was to investigate the relationship between the severity of dental caries and quality of life in pre-school children. Materials and Methods: This cross-sectional descriptive study was conducted on 145 parents and preschool children aged 2-5 years old referring to Ahvaz dental school and a pediatric dentistry office in Ahvaz city. The convenient sampling method was used and participants were patients referred to the faculty of dentistry and one pediatric dentistry office in Ahvaz. Early Childhood Oral Health Impact Scale (ECOHIS) questionnaire was used to evaluate the oral health related quality of life. The demographic information and dmft index (decayed, missing, and filled teeth) was assessed for children. Statistical analyzes included descriptive statistics, Spearman and Pearson tests. Results: The mean age of children was 4.12 ± 1.2 years. 72 children (49.65%) were boys and 73 of children (50.34%) were girls. Based on our results the mean ECOHIS score was 39.69 ± 18.95. There was a significant correlation between decreased quality of life and the lower age of the children (P=0.047), less parental education (P=0.018), more dmft score (P=0.000). Conclusion: It can be concluded that severity of dental caries is effective on children's quality of life. The quality of life of children decreases with the increase in the dmft, lower socio-economic status of parents, and higher age of parents.